Figs. 1–7 in New and little known for the fauna of Kunashir and Sakhalin Islands Lasiocampidae and Noctuoidea (Lepidoptera) - Rybalkin, S.A.; Yakovlev, R.V.; Benedek, B. (Zenodo, 2018)
Figs. 1–7. Imago of Lepidoptera from the Russian Far East (coll. S. Rybalkin): 1 ‒ Gas- Published as part of Rybalkin, S.A., Yakovlev, R.V. & Benedek, B., 2018, New and little known for the fauna of Kunashir and Sakhalin Islands Lasiocampidae and Noctuoidea (Lepidoptera), pp. 18-22 in Far Eastern Entomologist 355 on page 20, DOI:10.25221/fee.355.3, http://zenodo.org/record/7164421